Self-compassion and its relationship to sports psychological frustration of football club players in Nineveh Governorate - ايمن وليد احمد الطائي أ.د. ثامر محمود ذنون الحمداني (physical education and sport sciences college for women/ Baghdad University, 2021)
The topic of self-compassion and sports psychological frustration is one of the important topics in sports psychology, and for this it has received the attention of many scholars and researchers, hence the current research that seeks to build and apply the scale of self-compassion and sports psychological frustration for football club players in Nineveh Governorate, and the research relied on  The descriptive approach, as the total research community included 320 players from Nineveh Governorate.  The current research aims to:  - Knowing the degree of compassion in particular among football club players in Nineveh Governorate.                                                                                                                       - Knowing the degree of sports psychological frustration of football club players in Nineveh Governorate.  - - Identifying the correlation between self-pity and sports psychological frustration among football club players in Nineveh Governorate.  In light of the research results, the researchers concluded the following:          - In general, football club players in Nineveh Governorate enjoy a positive degree of compassion and compassion for themselves.  - In general, football club players in Nineveh governorate suffer from a somewhat high degree of psychological sports frustration.  -- The presence of a significant (opposite) relationship between self-pity and sports psychological frustration in the research sample, where the higher the degree of self-compassion corresponds to a decrease in the degree of sports psychological frustration among football club players in Nineveh Governorate. : The researchers recommend the following  - Designing a mentoring program based on self-compassion to alleviate the psychological frustration of sports among soccer players- Conducting counseling training courses in sports clubs by the sports psychological counselor to clarify the importance of self-pity in dealing with athlete failures.  - Conducting studies on self-pity, sympathy and tolerance for oneself and others among players of individual and combat games.